1998
DOI: 10.4141/a97-119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical treatment of whole canola seeds on carcass composition and blood lipids of lambs fed grass silage

Abstract: Huard, S., Seoane, J. R., Petit, H. V., Fahmy, M. H. and Rioux, R. 1998. Effects of mechanical treatment of whole canola seeds on carcass composition and blood lipids of lambs fed grass silage. Can. J. Anim. Sci. 78: 665-671. Thirty-three lambs (25.2 ± 2.7 kg BW) were used to study if mechanical treatment of canola seeds can exert an effect on carcass quality, blood lipids, and fatty acid profile of depot fat. All lambs received a basal diet of 179 g d -1 of a 16% CP commercial concentrate and grass silage fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Previously, the in vitro biohydrogenation rate of 18:1c-9 was reportedly similar between raw and extruded canola, being half that of PUFA (Enjalbert et al, 2003). When feeding ruminants processed canola, the lower biohydrogenation rate and higher intestinal absorption of 18:1c-9 has resulted in an appreciable transfer to milk (Tymchuk et al, 1998) and adipose tissue (Huard et al, 1998). In agreement with the CLA index, higher concentrations of 14:1c-9 and 16:1c-9 associated with the Trial 1 canola diet, as shown in Tables 2 and 3, suggest a reduction in SCD activity caused by the higher dietary PUFA levels of the linseed and soya bean diets.…”
Section: Total Lipidsmentioning
confidence: 99%
“…Previously, the in vitro biohydrogenation rate of 18:1c-9 was reportedly similar between raw and extruded canola, being half that of PUFA (Enjalbert et al, 2003). When feeding ruminants processed canola, the lower biohydrogenation rate and higher intestinal absorption of 18:1c-9 has resulted in an appreciable transfer to milk (Tymchuk et al, 1998) and adipose tissue (Huard et al, 1998). In agreement with the CLA index, higher concentrations of 14:1c-9 and 16:1c-9 associated with the Trial 1 canola diet, as shown in Tables 2 and 3, suggest a reduction in SCD activity caused by the higher dietary PUFA levels of the linseed and soya bean diets.…”
Section: Total Lipidsmentioning
confidence: 99%